Effect of different ozone treatments on the degradation of deoxynivalenol and flour quality in Fusarium-contaminated wheat. Issue 1 (1st January 2020) - Zhuang, Kun; Zhang, Chen; Zhang, Wei; Xu, Wei; Tao, Qian; Wang, Guozheng; Wang, Yuehui; Ding, Wenping
ABSTRACT: Deoxynivalenol (DON) in wheat (Emai596) was degraded by five ways of ozone treatments, including ozone-gas treated wheat flour, wheat kernels before and after tempering, and tempering and washing with ozonated-water. For lab-scale milling, the effect on flour quality was investigated. The DON was quantified via high-performance liquid chromatography after extraction with immunoaffinity columns. The measure indicated all treatments could decrease the DON content of flour below 1.00 mg/kg. Ozone-gas treated wheat kernels after tempering had the highest DON degradation rate 33.33%. Ozonation produced no significant difference in gluten qualities, dynamic viscoelasticity, pasting and mixing properties, when wheat kernels were treated with ozone-gas or ozonated-water. Although ozone-gas treated flour had the highest whiteness (85.56), but it had negative effect on the rest of quality indicators. The results suggested the treatment of Ozone-gas treated tempered wheat kernels could not only degrade DON most efficiently but also ensure quality of flour.